THE EFFECT OF THE EFFECTIVENESS OF INTERNAL CONTROLS, INFORMATION ASYMETRIES, ORGANIZATIONAL ETHICAL CULTURE AND PROCEDURAL JUSTICE ON THE TRENDS OF ACCOUNTING FRAUD IN VILLAGE GOVERNMENTS IN GATAK DISTRICT, SUKOHARJO REGENCY - Itsney Nur Hikmah; Suhesti Ningsih; Hasan Ma'ruf (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Accounting fraud occurs in the form of financial statement misstatements, abuse of authority by refusing information by accounting management in the government, including in the village government. This study aims to determine the effect of internal control effectiveness, information asymmetry, organizational ethical culture, and procedural justice on the tendency of accounting fraud in the Village Government of Gatak District, Sukoharjo Regency. This research is a quantitative descriptive research. The data collection technique used an instrument in the form of a closed questionnaire with a Likert scale and documentation. The sample in this study was all village heads, village treasurers, BPD heads, BPD deputy chairmen and village BPD treasurers throughout Gatak District, Sukoharjo Regency with a total of 70 people taken by total sampling. The data analysis method used multiple linear regression analysis. The results showed that there was a significant negative effect on the effectiveness of internal control on the tendency of accounting fraud, information asymmetry had a significant positive effect on the tendency of accounting fraud, organizational ethical culture had a significant negative effect on the tendency of accounting fraud and procedural justice had a significant negative effect to the tendency of accounting fraud